Role of abscisic acid in regulating fruit set and ripening in squash (Cucurbita pepo L.). Issue 4 (1st October 2016) - Chen, P; Pei, YL; Liang, B; Zhang, YS; Zhai, XW; He, SH; Kai, WB; Sun, YF; Leng, P
ABSTRACT: Squash is a non-climacteric fruit, so the release of ethylene plays a limited role in the ripening process; however, there is a large accumulation of abscisic acid (ABA) during fruit maturation and ripening. To investigate the contribution of ABA in squash fruit development, the CpNCED1 gene, which encodes the key enzyme in ABA biosynthesis (9-cis-epoxycarotenoid dioxygenase [NCED]), was cloned from squash fruit, and its transcriptional regulation during fruit development, dehydration and pollination was analysed using a quantitative reverse transcription polymerase chain reaction (qRT-PCR). The expression of CpNCED1 peaked 20 days after full bloom (DAFB) in the pulp and seed, and 25 DAFB in the peel, all of which corresponded with the accumulation of ABA. The application of exogenous ABA increased the expression of CpNCED1 and the release of ethylene, thereby promoting fruit ripening. The expression of CpNCED1 was also induced by dehydration stress and pollination. These findings show that ABA plays important roles in squash fruit ripening, and in the plant's response to dehydration stress and early fruit set via the transcriptional regulation of CpNCED1 .